PENGEMBANGAN COSTI (COFFEE SNACK PURWABAKTI) UNTUK MENINGKATKAN UMKM DI DESA PURWABAKTI - Melinasari, Susi; Syamsiah, Yayah; Putra Aliza, M Ozama; Pulungan, Adilah Rahma (LPPM Universitas Al Muslim, 2024)
This community service activity aimed to determine the local potential of the Purwabakti Village area which can be used as a village innovation. This activity is carried out in Purwabakti Village from August to September 2024. Training participants consisted of village officials and residents of Purwabakti Village. Implementation of activities used the outreach method. The method of implementing the activities was carried out through the observation stage which was carried out in August, and training in making Purwabakti Coffee Snacks in September. From the results of the implementation of community service activities, it can be seen that the majority of the community has high enthusiasm for developing COSTI (Coffee Snack Purwabakti). This can be seen from the outreach activities regarding COSTI which opens up financial space for the community by using local coffee as a snack based on village innovation, thus helping MSMEs in the village to be productive and innovative in the products they manage and market, with the aim of increasing income and welfare of the people of Purwabakti Village.